Answer:
x = 3 , y = 1
Step-by-step explanation:
Solve the following system:
{4 x - 3 y = 9 | (equation 1)
10 y = 2 x + 4 | (equation 2)
Express the system in standard form:
{4 x - 3 y = 9 | (equation 1)
-(2 x) + 10 y = 4 | (equation 2)
Add 1/2 × (equation 1) to equation 2:
{4 x - 3 y = 9 | (equation 1)
0 x+(17 y)/2 = 17/2 | (equation 2)
Multiply equation 2 by 2/17:
{4 x - 3 y = 9 | (equation 1)
0 x+y = 1 | (equation 2)
Add 3 × (equation 2) to equation 1:
{4 x+0 y = 12 | (equation 1)
0 x+y = 1 | (equation 2)
Divide equation 1 by 4:
{x+0 y = 3 | (equation 1)
0 x+y = 1 | (equation 2)
Collect results:
Answer: {x = 3 , y = 1